Predictors of satisfaction with life in family carers: evidence from the third European quality of life survey - De Oliveira, Deborah Christina; Hlebec, Valentina (University of Ljubljana, Faculty of Social Sciences, 2016)
This research aimed to identify predictors of satisfaction with life in family carers. Evidence from the literature and from the Third European Quality of Life Survey (years 2011–2012) led to the construction of a model which was tested through linear regression analysis. The results corroborate findings from previous studies identified in the literature, showing that married and employed carers with higher education, those with fewer difficulties making ends meet with their household income and those who are healthier have higher levels of satisfaction with life. Carers that participate in physical and social activities and have larger informal social support networks also have higher levels of satisfaction with life. Those reporting difficulties finding time to see a doctor for their own health due to their caregiving role and those experiencing difficulties in accessing formal long-term care have lower satisfaction with life. Policies aiming at balancing care and other activities, such as work, respite and activities in other life spheres, may have an important influence on informal carers’ quality of life.